Discordance Between Spine-Hip and Paretic-Nonparetic Hip Bone Mineral Density in Hemiplegic Stroke Patients: A Multicenter Retrospective Study - Seung Don Yoo; Tae-Woo Kim; Byung-Mo Oh; Seung Ah Lee; Chanwoo Kim; Ho Yeon Chung; Jung Eun Son; Ji Yeon Lee; Hyunji Lee; Hoo Young Lee (Annals of Rehabilitation Medicine)
Objective To identify the prevalence and factors associated with T-score discordance between the spine and hip, as well as between the paretic and non-paretic hips in hemiplegic stroke patients, this study investigated bone mineral density (BMD) patterns. Bone loss predominantly affects the paretic hip after a stroke, and typical clinical assessments using dual-energy X-ray absorptiometry (DXA) that scan the lumbar spine (LS) and a single hip may overlook an osteoporosis diagnosis. This oversight could potentially lead to suboptimal treatment for stroke patients. Methods This study was a multicenter retrospective analysis of 540 patients admitted for stroke rehabilitation between October 2014 and February 2022, who underwent DXA of LS and bilateral hips. Results The prevalence rates of concordance, low LS discordance, and low hip discordance between the LS and hips were 48.2%, 12.2%, and 39.6%, respectively. The discordance rate between bilateral hips was 17.0%. The paretic side had significantly lower total hip T-scores than the non-paretic side (p<0.001). Notably low paretic hip discordance was more prevalent during the chronic phase. DXA scans of the LS and both hips revealed a 0.7%–0.9% higher major discordance compared to LS and single hip DXA scans. The multivariate analysis revealed a significant correlation between a low paretic hip discordance and cognitive impairment (adjusted odds ratio 0.071, 95% confidence interval 0.931–1.003, p<0.05). Conclusion Since stroke survivors are at high risk for hip fractures, comprehensive BMD assessments, which include LS and bilateral hips, should be considered for post-stroke osteoporosis care to enhance diagnostic accuracy and timely treatment.